Penguatan Keberaksaraan Warga Belajar Tuntas Aksara Melalui Keaksaraan Usaha Mandiri (KUM) di Pesisir Kabupaten Jember - Linda Fajarwati; Lutfi Ariefianto; Muhammad Irfan Hilmi (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The paradigm of script or literacy does not only encompass basic literacy, which includes the ability to read, write, and calculate. Nowadays, script or literacy can be understood as the individual's ability and skills to access personal potential, their environment, and solve problems necessary in daily life. This service aims to strengthen literacy for learners who have completed basic literacy through independent literacy activities (KUM), which is a learning activity based on independent efforts, learning and striving, and learning that results. his method is one of the strategies used to address the problem of re-emerging illiteracy that occurs among learners who have completed basic literacy. The activity is carried out in several stages. The planning consists of three steps, namely: making agreements with partners, collaborating with successful entrepreneurs/models, and designing mentoring with partners. In the implementation phase, the mentoring is carried out in 3 stages, namely: strengthening reading, writing, and arithmetic skills; providing skills based on local potential and strategies for business development; and mentoring for independent business groups. The evaluation includes both learning evaluation and program evaluation. The results of the independent business literacy program include several outcomes: sustained reading, writing, and arithmetic skills for functional literacy learners, the development of skills to process local coastal resources, and the ability to run independent businesses to support the community's economy through independent business literacy.